Cyanoacrylate glue-assisted endoscopic extraction of a large esophageal stone in an adult - Deshidi, Srinu; Mahajan, Gaurav; Kamisetty, Viswanath; Kolla, Spoorthi; Gongati, Venu; Gongala, Harsha vardhan Reddy; Kante, Bhaskar; Appasani, Sreekanth (Indian Journal of Case Reports, 2025)
Foreign body ingestion is a common reason for emergency department visits, particularly in children, but also occurs in adults with psychiatric disorders, cognitive impairment, or intoxication. We report the case of a 30-year-old male with intellectual developmental disorder who presented with chest pain and dysphagia following ingestion of a large stone. Imaging revealed a triangular-shaped opacity in the superior mediastinum, and endoscopy confirmed a large stone in the upper esophagus. Initial attempts to grasp the stone using a snare were unsuccessful due to its slippery surface and lack of adequate space to fully open the instrument. The stone was gently pushed into the stomach and attempted removal using rat-tooth forceps, retrieval nets, basket, and snare, but these were unsuccessful due to the stone’s large size and slippery surface, where application of n-butyl-2-cyanoacrylate glue created a rough surface that enabled secure grasping with a polypectomy snare. The stone was successfully extracted, with only minor mucosal injury. This case demonstrates the innovative use of cyanoacrylate glue as an adjunct to facilitate endoscopic removal of slippery foreign bodies.